ANALISIS KELAYAKAN EKONOMI TAMBANG BENTONIT MENGGUNAKAN METODE DISCOUNTED CASH FLOW - Wahyuni Wahyuni; Diana Purwandari; Tati Febrianti Syantika Rini (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research was conducted to analyze and evaluate the feasibility of the bentonite mining business carried out by CV. Bentonit Ariyanto. The calculations in this research use Discounted Cash Flow (DCF). Discounted Cash Flow (DCF) is a cash flow calculation method that calculates the time value of money. Money invested in the present will have a different value in the future. From the calculation results using the Discounted Cash Flow method CV. BENTONIT ARIYANTO has a Net Present Value (NPV) of 2,864,612,232 > 0, Payback Period (PBP) 6 years 9 months < Age of Mine, Internal Rate of Return (IRR) 17.48% > MARR, Profitability Index (PI) 1, 95 > 1 and Sensitivity Analysis has a value when the selling price falls 5% and costs remain the same, the NPV value is 1,741,946,278, IRR 15.97%, PBP 9 years 1 month, PI 1.58. When the selling price falls 15% and costs remain the same, the NPV value is -503,385,631, IRR 10.78%, PBP 10 years 5 months, PI 0.83. When the selling price increases by 12.5% ​​from the current selling price and costs remain the same, the NPV value is 5,671,277,118, IRR 19.9%, PBP 4 years 3 months, and PI 2.89